A low‐cost environmental chamber to simulate warm climatic conditions. Issue 1 (14th April 2020) - Darehshouri, Sahand; Michelsen, Nils; Schüth, Christoph; Schulz, Stephan
Abstract: Environmental chambers are used for a variety of experiments in multiple disciplines but are often prohibitively expensive. In this study, we developed an environmental chamber that allows reliable regulation of temperature and relative humidity in a range typical for warm climatic conditions. As we have only used consumer products, which are readily available off the shelf, the device is affordable (<€900) and easy to replicate. The presented chamber has inner dimensions of 1, 790 × 970 × 520 mm (height × width × depth). It is heated with two infrared lamps, and for moistening, an ultrasonic mister is used. Air dehumidification and cooling down to ambient temperature are realized with inflowing compressed laboratory air. Additionally, we installed a Peltier element cooling system to enable temperatures below the ambient laboratory temperature. The chamber works in a temperature and humidity range of 15–50 °C and 10–95%, respectively. Core Ideas: We develop a low‐cost environmental chamber to simulate warm climatic conditions. It allows the regulation of temperature (15–50 °C) and relative humidity (10–95%). All parts are available off the shelf. It is affordable (<€900) and easy to replicate.